2005
DOI: 10.1113/expphysiol.2004.029728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co‐supplementation of vitamins E and C on gentamicin‐induced nephrotoxicity in rat

Abstract: Gentamicin (GM) is an effective antibiotic against severe gram-negative infections. However it can produce nephrotoxicity in human. Reactive oxygen species (ROS) have been proposed as the causative factors of the renal side effects the drug. This study was performed to investigate the protective role of antioxidant vitamins against GM-mediated nephropathy in an in situ model of isolated rat kidney. Male Sprague-Dawley rats were randomly assigned to one of the following groups of seven rats: group 1 (Control) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 24 publications
(30 reference statements)
3
66
0
Order By: Relevance
“…It has been shown that GM exerts its adverse renal effect by generation of ROS 37) which results in sever tissue damage. 38) Under normal conditions, ROS, which are generated during cellular functions, are eliminated by intrinsic antioxidant enzyme systems like superoxide dismutase, catalase and glutathione peroxidase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that GM exerts its adverse renal effect by generation of ROS 37) which results in sever tissue damage. 38) Under normal conditions, ROS, which are generated during cellular functions, are eliminated by intrinsic antioxidant enzyme systems like superoxide dismutase, catalase and glutathione peroxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ATP depletion from either mitochondrial damage or direct inhibition of mitochondrial oxidative phosphorylation (17-21) and reactive oxygen species (ROS) production are other mechanism take part in nephrotoxicity (18)(19)(20). Most studies reported previously were designed to administer drugs before or at the same time of renal insult (18)(19)(20)(21)(22)(23)(24). However, most therapeutic agents are usually administered after the expression of clinical diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has some nephrotoxicity which causes limitations in the extent of its use. In recent years there have been many studies on the mechanisms of GM-induced nephrotoxicity and reduction of the renal damage caused by it (3,4). issue of journal, the effects of erythropoietin on amelioration of gentamicin-induced renal toxicity was investigated by biochemical and histopathological indices (5).…”
mentioning
confidence: 99%